Monotone Sequences

The Monotone Sequence Theorem is one of only two major mechanisms by which it's possible to prove that a sequence converges without having to explicitly know what the value of the limit is.
Theorem (Monotone Sequence Theorem)
Suppose that \(\{a_n\}_{n=1}^\infty\) is a nondecreasing sequence which is bounded above. Then
\[ \lim_{n \rightarrow \infty} a_n = \sup \{ a_n \ : \ n \in {\mathbb N} \}, \]
i.e., the limit exists and is equal to the supremum of the set of terms. Similarly, if \(\{b_n\}_{n=1}^\infty\) is a nonincreasing sequence which is bounded below, then
\[ \lim_{n \rightarrow \infty} b_n = \sup \{ b_n \ : \ n \in {\mathbb N} \}. \]
Proof
Meta (Main Idea)
For the nondecreasing sequence, let
\[ L := \sup \{ a_n \ : \ n \in {\mathbb N} \}. \]
The supremum exists because the set is nonempty and bounded above by hypothesis. For each \(\epsilon > 0\), we know that there is some element \(a_N\) of the set which is not much smaller than the supremum, i.e., such that \(a_N > L - \epsilon\). Because the sequence is nondecreasing, for any \(n \geq N\), \(a_n \geq a_N > L - \epsilon\). But by definition of the supremum, we also know that none of the terms are larger than the supremum, i.e., \(a_n \leq L\) as well. Thus \(L - \epsilon < a_n \leq L < L + \epsilon\). Subtracting \(L\) from each part implies that \(|a_n - L| < \epsilon\) for all \(n \geq N\) as desired.

1. Example: Defining \(k\)-th roots of positive real numbers

Theorem
For each nonnegative real number \(A\) and every positive integer \(k\), there is a real number \(x\) such that \(x^k = A\).
Proof
Meta (Main Idea)
Use the Method of Bisection. Below is an illustration of this method. We have one “guess” \(a_n\) which is known to be too small and a second “guess” \(b_n\) known to be too big. From this pair, we make a new pair of guesses closer together by defining \(a_{n+1}\) and \(b_{n+1}\) so that \([a_{n+1},b_{n+1}]\) is either the left or right half of the interval \([a_n,b_n]\). We make the choice so that the left endpoint is never too large and the right endpoint is never too small. The first figure below illustrates several steps of the method of bisection and the second reiterates how \(a_{n+1}\) and \(b_{n+1}\) are defined in terms of \(a_n\) and \(b_n\).
Figure. Several Successive Stages of Bisection
Figure. Rules of the Method of Bisection

Let \(A \geq 0\). If we define
\[ a_0 := 0 \text{ and } b_0 := (1 + A) \]
We know that \(a_0^k = 0 \leq A\) and \(b_0^k \geq 1 + k A \geq A\), i.e., the \(k\)-th power of \(A\) is too small and the \(k\)-th power of \(b_0\) is too large. The \(k\)-th power of the midpoint \((a_0+b_0)/2\) will either be \(\leq A\) or \(\geq A\). In the former case, let \(a_1 := (a_0+b_0)/2\) and \(b_1 := b_0\); in the latter case let \(a_1 := a_0\) and \(b_1 := (a_0 + b_0)/2\). Repeat this process to define two sequences \(\{a_n\}_{n=0}^\infty\) and \(\{b_n\}_{n=0}^\infty\). Show by induction that
  • \(a_n \leq b_n\) for each \(n\)
  • \(a_n^k \leq A\) for each \(n\)
  • \(b_n^k \geq A\) for each \(n\)
  • \(\{a_n\}_{n=0}^\infty\) is nondecreasing
  • \(\{b_n\}_{n=0}^\infty\) is nonincreasing
  • \(b_n - a_n = 2^{-n}(1 + A)\) for each \(n\) These facts combined are enough to show that the sequence of \(a_n\)'s and the sequence of \(b_n\)'s both converge and have the same limit and that
    \[{}\lim_{n \rightarrow \infty} (a_n^k - A) {}\]
    \[{}\leq 0{}\]
    \[{}\leq \lim_{n \rightarrow \infty} (b_n^k-A);{}\]
    then use the limit law \(\lim_{n \rightarrow \infty} (a_n)^k = \left( \lim_{n \rightarrow \infty} a_n \right)^k\) to see that \(0 = (\lim_{n \rightarrow \infty} a_n)^k - A\).

2. Limsup and Liminf

Definition
Given any sequence \(\{a_n\}_{n=1}^\infty\), we can define its limit superior and limit inferior by
\[ \limsup_{n \rightarrow \infty} a_n := \inf_{N \geq 1} \sup_{n \geq N} a_n \]
and
\[ \liminf_{n \rightarrow \infty} a_n := \sup_{N \geq 1} \inf_{n \geq N} a_n. \]
The limsup and liminf are always defined as extended real numbers. If the sequence \(a_n\) is not bounded above, we interpret \(\sup_{n \geq N} a_n\) as \(+\infty\) and say that \(\limsup_{n \rightarrow \infty} a_n = \infty\). Likewise, if the sequence is not bounded below, then we understand \(\liminf_{n \rightarrow \infty} a_n = -\infty\).
Theorem
For any sequence \(\{a_n\}_{n=1}^\infty\),
\[ \liminf_{n \rightarrow \infty} a_n \leq \limsup_{n \rightarrow \infty} a_n. \]
The limsup and liminf are equal and finite if and only if the sequence converges; in this case, the limsup and liminf simply equal the limit. Both limsup and liminf are \(+\infty\) if and only if the sequence diverges to \(+\infty\), and both are equal to \(-\infty\) iff the sequence diverges to \(-\infty\).
Proof
Meta (Key Ideas)
To prove the inequality, observe that
\[ \inf_{n \geq N} a_n \leq \sup_{n \geq M} a_n \]
for each value of \(N\) and \(M\), because one can compare both to \(a_n\) for some \(n \geq \max\{N,M\}\). This means that \(\sup_{n \geq M} a_n\) is an upper bound for the set \(\{\inf_{n \geq N} a_n \ : N \geq 1\}\) and so must be greater than or equal to its supremum (if \(\sup_{n \geq M} a_n\) is infinite for all \(M\), then there's nothing to prove because the limsup will be \(+\infty\) which is never strictly smaller than anything; the analogous statement is also true if \(\inf_{n \geq N} a_n = -\infty\) for all \(N\)). Thus
\[ \sup_{N \geq 1} \inf_{n \geq N} a_n \leq \sup_{n \geq M} a_n. \]
Now repeat; the liminf is a lower bound for the right-hand side, so must be smaller than or equal to the infimum of the right-hand side.

Notice that when \(\limsup_{n \rightarrow \infty} a_n = L\) for some finite \(L\), this means that \(\inf_{N \geq 1} \sup_{n \geq N} a_n = L\). For any positive \(\epsilon\), there must be some \(N\) such that \(\sup_{n \geq N} a_n < L + \epsilon\). That implies, in turn, that \(a_n < L + \epsilon\) for each \(n \geq N\). Similarly, if \(\liminf_{n \rightarrow \infty} a_n = L'\) for some finite \(L'\), then \(a_n > L' - \epsilon\) for all \(n \geq N'\) for some \(N' \in {\mathbb N}\). This is the main observation for proving the relationship to the limit.

Note conversely that if for all \(\epsilon > 0\), there is some \(N\) such that \(a_n < L + \epsilon\), this means that \(\sup_{n \geq N'} a_n \leq L + \epsilon\) for all \(N'\) sufficiently large. This would mean that the infimum also needs to be less than or equal to \(L+ \epsilon\), i.e. it would imply \(\limsup_{n \rightarrow \infty} a_n \leq L + \epsilon\) for each \(L > 0\). That forces \(\limsup_{n \rightarrow \infty} a_n \leq L\). A symmetric argument applies for asymptotic lower bounds and the liminf.
Exercises
  1. Let \(a_1 := 0\) and for each \(n > 1\), let \(a_n := \sqrt{3 + 2a_{n-1}}\). Prove that this sequence is monotone increasing and converges.
  2. Let \(b_n := \frac{1}{n^2} + (-1)^n \frac{1+n}{n}\). Compute \(\limsup_{n \rightarrow \infty} b_n\) and \(\liminf_{n \rightarrow \infty} b_n\) (and prove your answer).